A Tuning Fork Frequency Up-Conversion Energy Harvester - Qinghe Wu (MDPI AG, 2021)
In this paper, a novel tuning fork structure for self-frequency up-conversion is proposed. The structure has an in-phase vibration mode and an anti-phase vibration mode. The in-phase vibration mode is used to sense the environment vibration, and the anti-phase vibration mode is used for energy conversion and power generation. The low-frequency energy collection and the high-frequency energy conversion can be achieved simultaneously. Theoretical and experimental results show that the tuning fork frequency up-conversion energy harvester has excellent performance. This structure provides the energy harvester with excellent output power in a low-frequency vibration environment. At the resonant frequency of 7.3 Hz under 0.7 g acceleration, the peak voltage is 41.8 V and the peak power is 8.74 mW. The tuning fork frequency up-conversion energy harvester causes the humidity sensor to work stably. The structure has the potential to power wireless sensor nodes or to be used as a small portable vibration storage device, especially suitable for the monitoring of the environment related to human movement.